2012
DOI: 10.1038/oby.2011.396
|View full text |Cite
|
Sign up to set email alerts
|

Visceral and Not Subcutaneous Abdominal Adiposity Reduction Drives the Benefits of a 1‐Year Lifestyle Modification Program

Abstract: Excess visceral adipose tissue (VAT) is associated with an increased cardiometabolic risk. The study examined whether changes in cardiometabolic risk markers after a 1-year lifestyle intervention in viscerally obese men were associated with changes in VAT or with changes in subcutaneous abdominal adipose tissue (SAT). The relative contributions of changes in global adiposity vs. changes in cardiorespiratory fitness to changes in VAT were also quantified. One hundred and forty four men were selected on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 42 publications
3
52
1
1
Order By: Relevance
“…Weight loss studies have shown that visceral fat loss is related to cardiometabolic improvement [18,19]. Recently, Rittig et al [20] demonstrated that only visceral fat loss and not body weight loss or total fat loss was associated with improvement in endothelial function in T2DM-prone participants who were involved in a 9-month lifestyle intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss studies have shown that visceral fat loss is related to cardiometabolic improvement [18,19]. Recently, Rittig et al [20] demonstrated that only visceral fat loss and not body weight loss or total fat loss was associated with improvement in endothelial function in T2DM-prone participants who were involved in a 9-month lifestyle intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Several intervention studies using a combination of physical activity/exercise and moderate caloric restriction have reported a preferential mobilization of visceral/ ectopic fat beyond what could be predicted from weight loss. 134,138 Such findings are promising and may eventually influence the choice of simple adiposity metrics such as waist circumference to be used in preventive cardiology as markers of cardiovascular health and as therapeutic adiposity targets. In addition, overweight/obese patients are often characterized by a low level of cardiorespiratory fitness, 139 which is largely a marker of their sedentary lifestyle.…”
Section: Assessing and Managing High-risk Obesity In Cardiology: Goinmentioning
confidence: 99%
“…14,15) It has not previously been shown whether CR changes VAT/SAT volume and skeletal muscle mass in patients with CHF, although several studies have shown that exercise and lifestyle modification reduce VAT in patients with diabetes, hyperlipidemia, and obesity without CHF. [16][17][18] The accumulation of abdominal fat leads to the accumulation of cardiovascular risk factors, including insulin resistance, lipid abnormalities, and abnormalities of muscle metabolism. 13,19,20) In this study, most of the patients are affected with metabolic syndrome as well as CHF.…”
Section: Discussionmentioning
confidence: 99%